Dr. Louis Isaac Woolf: At the Forefront of Newborn Screening and the Diet to Treat Phenylketonuria-Biography to Mark His 100th Birthday † - José Ramón Alonso-Fernández (MDPI AG, 2020)
In mid 2019, the author reminded the (International Society for Neonatal Screening) ISNS of the happy occasion of the 100th birthday of one of the living pioneers of neonatal screening, Professor Louis Isaac Woolf [...]